PENINGKATAN MUTU PENDIDIKAN PEMBELAJARAN BAHASA INDONESIA MELALUI PROGRAM PENUGASAN DOSEN DI SEKOLAH DASAR NEGERI 04 KOTABUMI LAMPUNG - Nur Mei Ningsih (Edukasi Lingua Sastra, 2019)
The improvment of education in Indonesia should be done soon, because the quality of education in Indonesia is lower than others. To improve the quality of Indonesian teacher is by improving the collaboration of teacher competence by Training Lecturer Program at School. This activity will bring the positif effect to high school and the aim school. This program needs lecturer’s commitment to be a teacher in aim school. This activity becomes a new experience and it’s not easy to be done by a lecturer. The lecturer has a new habit there because it is different from their usuall habit. The purposes of Training Lecturer Program at School (1) giving a new experience in uderstanding and developing the students’ character, managing the activity of learning at school, and comprehending daily experience and sociocultural of society: (2) producting the device of collaborative learning between lecturer and teacher at aim school; (3 ) creating the quality of learning by making good atmosphere, the quality of device learning, and improving the successful of students; (4) improvement the relationship between high school with the aim school in all forms of the quality of learning. By Training Lecturer Program at School, it hopes could improve the quality of education.